Understanding Consumer Behavior in Live Streaming E-Commerce: A Technology Acceptance Model Perspective - Herlina, Herlina; Andry, Johanes Fernandes; Mulyana, Teady Matius Surya; Wilujeng, Fuji Rahayu; Sasongko, Yohanes Probo Dwi; Rachmad, Teguh Hidayatul (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2025)
Live streaming has rapidly become a transformative feature within the landscape of online shopping, not only serving as an interactive marketing tool but also reshaping consumer decision-making processes in the digital marketplace. Far beyond a mere add-on, live streaming represents a disruptive innovation that significantly alters consumer–vendor engagement and accelerates the evolution of e-commerce ecosystems. To gain a deeper understanding of this phenomenon, the present study employs the Technology Acceptance Model (TAM) as a theoretical lens to investigate the drivers of consumer adoption and sustained usage of live streaming in online shopping contexts. Data were collected from 150 active users of live streaming features through purposive accidental sampling and analyzed using path analysis with AMOS software. The results provide strong empirical evidence that the TAM constructs Perceived Usefulness (PU), Perceived Ease of Use (PEU), Attitude Toward Using (ATU), Behavioral Intention to Use (BIU), and Actual System Use (AU) are all significantly and positively interrelated. These findings underscore the strategic importance of consumer perceptions of utility and ease of use in fostering favorable attitudes, strengthening behavioral intentions, and translating into actual system usage. This research not only validates TAM in the context of live streaming but also offers critical implications for global e-commerce stakeholders and technology developers by highlighting how interactive features can be optimized to enhance consumer engagement, trust, and long-term digital marketplace sustainability.